2017
DOI: 10.1002/14651858.cd006612.pub5
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine-lowering interventions for preventing cardiovascular events

Abstract: In this third update of the Cochrane review, there were no differences in effects of homocysteine-lowering interventions in the form of supplements of vitamins B6, B9 or B12 given alone or in combination comparing with placebo on myocardial infarction, death from any cause or adverse events. In terms of stroke, this review found a small difference in effect favouring to homocysteine-lowering interventions in the form of supplements of vitamins B6, B9 or B12 given alone or in combination comparing with placebo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
107
1
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(119 citation statements)
references
References 210 publications
2
107
1
9
Order By: Relevance
“…There has been much interest in researching whether lowering serum homocysteine levels has a beneficial effect on cardiovascular disease. One recent meta-analysis of randomized-controlled trials studying the effect of B12, B9, and/or B6 supplementation, which lowers blood homocysteine, found no evidence that supplementation prevents myocardial infarction or lowers mortality rates in those living with cardiovascular disease, while antihypertensives combined with a homocysteine-lowering regimen may reduce stroke (Martí-Carvajal et al, 2017). …”
Section: Resultsmentioning
confidence: 99%
“…There has been much interest in researching whether lowering serum homocysteine levels has a beneficial effect on cardiovascular disease. One recent meta-analysis of randomized-controlled trials studying the effect of B12, B9, and/or B6 supplementation, which lowers blood homocysteine, found no evidence that supplementation prevents myocardial infarction or lowers mortality rates in those living with cardiovascular disease, while antihypertensives combined with a homocysteine-lowering regimen may reduce stroke (Martí-Carvajal et al, 2017). …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, previous randomized trials focused on the risk of CAD from Hcy failed to demonstrate the effect of Hcy-lowering for a role for primary and secondary prevention [8,[11][12][13]. A recent review and meta-analysis of 15 randomized trials involving 71,422 patients with high Hcy levels regarding the prevention of CVD, found no differences between Hcy-lowering therapy and placebo groups regarding the incidence of myocardial infarction (risk ratio [RR] 1.02; 95% CI 0.95-1.10) or all-cause death (RR 1.01; 95% CI 0.86-1.06), except for a modest prevention of stroke, which was reduced by 10% (RR 0.90; 95% CI 0.82-0.99) [14]. In the current study, after adjustment for clinical and laboratory variables, no association was found between Hcy levels and subclinical coronary atherosclerosis on CCTA.…”
Section: Plos Onementioning
confidence: 99%
“…Several randomized trials did not demonstrate the clinical benefit of Hcy-lowering therapy in CAD prevention [8,[11][12][13]. In addition, a recent meta-analysis has not shown an association of Hcy-lowering treatment with the incidence of all-cause death or CAD, except a modest prevention of stroke [14]. Therefore, it remains unclear whether Hcy is a risk factor for CAD.…”
Section: Introductionmentioning
confidence: 99%
“…В связи с этим, проводятся исследования по гомоцистеин-снижающей витаминотерапии. Результаты исследований противоречивы и требуют дальнейшего накопления материалов [5,12].…”
Section: Aimunclassified
“…Увеличение содержания гомоцистеина в крови оказывает повреждающее действие на эндотелий сосудов и стимулирует тромбообразование [4]. Частота встречаемости ГГЦ в общей популяции составляет 5-10% [5], у пожилых эти показатели выше и составляют 30-40% [5]. У больных с острым инфарктом миокарда (ОИМ) при стенозирующем коронарном атеросклерозе (СКА) уровень гомоцистеина выше референтных значений в 75% случаев [6].…”
unclassified